Iron Age cemetery in Kobarid (Slovenia): investigations in 1979 - Kruh, Ana (Arheološki vestnik, 2022)
The size and discovered remains of an Iron Age cemetery rank Kobarid among the most important Slovenian prehistoric sites and one of the centres of the Sveta Lucija group. The cemetery extended across the terraces on the right bank of the River Soča, at the foot of the Gradič hill. It was discovered as early as the 1880s. The earliest archaeological excavations, between 1886 and 1904, were conducted by Carlo Marchesetti, the then director of Museo Civico di Storia Naturale di Trieste; the later investigations were carried out by archaeologists of Narodni muzej in Ljubljana, and Goriški muzej and Tolminski muzej. Although more than 1400 graves have been discovered, very little is known about them, because published data are scarce. This article presents the preliminary findings of the archaeological excavations conducted at the cemetery by a team of Goriški muzej in 1979. Although simultaneous construction work and unfavourable weather conditions made the excavations difficult, the team revealed 278 graves that date from the late 9th to the 5th century BC. Based on the analysis of these graves, this article provides a brief overview of the burial practice and the characteristic grave goods of the chronological phases of the Sv. Lucija group.